Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Ask your questions and receive precise answers from experienced professionals across different disciplines. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
You can factor out a 5 from the equation since all of the numbers are divisible by 5
5(x^2-x-6=0)
Factor into two binomials
5(x-3)(x+2)=0
Because of the zero product property, we know that one of the two binomials (in parenthesis) must equal 0.
x-3=0 and x+2=0
Solve each INDIVIDUALLY to find the values of x
x= 3 AND x= -2
5(x^2-x-6=0)
Factor into two binomials
5(x-3)(x+2)=0
Because of the zero product property, we know that one of the two binomials (in parenthesis) must equal 0.
x-3=0 and x+2=0
Solve each INDIVIDUALLY to find the values of x
x= 3 AND x= -2
[tex] 5x^2-5x-30=0\\
5(x^2-x-6)=0\\
5(x^2-3x+2x-6)=0\\
5(x(x-3)+2(x-3))=0\\
5(x+2)(x-3)=0\\
x=-2 \vee x=3
[/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.